The Media Business Model Of Solopos In Balancing The Achievement Of Its Market Performance With The Public Interest Performance - SURYAWATI, Indah; RUSADI, Udi; WAHID, Umaimah (International Journal of Environmental, Sustainability, and Social Science, 2023)
The transformation of newspapers to online and multiplatform is a necessity. Solopos Daily, as a local newspaper in the City of Solo, is rapidly presenting itself on online and multiplatform platforms to survive. Placing Harian Solopos as the case, the problem in this research is formulated as follows: (1) How is the media business model of Harian Solopos in balancing the achievement of market performance and public interest performance? Moreover, (2) How can the media business model maintain printed Solopos multiplatform?; The research method used is a holistic single case study with qualitative research. This research revealed that Harian Solopos realized that the era of digitalization technology was responsible for the decrease in the number of readers and advertisers. To overcome the problems, several innovations were implemented in its media business model. The performance of public interest showed that Solopos Daily has continuously carried out journalistic principles and is committed to maintaining the practices of dignified and polite journalism. This research has formulated a media business model concept that balances market performance with public interest performance.